INHIBITION TOUNGE CANCER PROLIFERATION OF HUMAN ORAL CELLS CULTURED SP-Cl USESPUKUL EMPAT LEAVES (Mirabilis jalapa L.) ETHANOLIC EXTRACT - , Cynthia Sylviana ([Yogyakarta] : Fak.Kedokteran Gigi Universitas Gadjah Mada, 2012)
Deciduous plants Mirabilisjalapa L.is an ornamental plants which has benefits for life. The leaves contain four RIP (Ribosom Inactivating Protein), which can inhibit the growth of cancer cells. This study aims to determine the ethanol ectract inhibitor of leaves of four in the proliferation of human oral tounge cancer cells Supri's Clone 1 (SP- Cl). Thistype of research is purely experimental research laboratory. This study using cultured cells of human tongue cancer (SP-Cl), human tongue cancer cell cultures (SP-Cl) was placed in 96 well plates and then added with various concentrations of ethanol extract of leaves of Mirabilisjalapa L.(7.5, is, 25, 50, 75 &micro